Analisis Penggunaan Literasi Digital Sebagai Media Pembelajaran Guru di SD Negeri 2 Tambun - Nasriani (PT FORMOSA CENDEKIA GLOBAL, 2022)
The type of research used is qualitative research which aims to describe the implementation of digital literacy as a learning medium by teachers. This research was conducted at the State Elementary School 2 Tambun with the research subjects namely the principal, teachers and students. Data collection techniques used are observation, interviews and documentation and research data analysis techniques using the pre-field stage, the field stage, and the data analysis stage obtained from the field. The results of the study show aspects of teacher training through the principal's instructions and also independently always follow training activities related to digital literacy and from the aspect of applying and implementing digital literacy teachers have implemented it in the learning process at school to students while from understanding they have understood and are able to use literacy. digital as a digital learning media.